Strategi Kepemimpinan dalam Memaksimalkan Pelayanan Digital Pasca Pandemi Covid-19 di GKE Bukit Hindu Palangka Raya - Inriani, Eva; Pebriasi, Elia (Institut Agama Kristen Negeri Palangka Raya, 2024)
The Covid-19 pandemic had provided lessons for churchs to have made service strategies that can adapted to the lifestyle in the pandemic era. Digital services are an alternative developed by churches and continue to be develoved by church ini Post Covid-19 pandemic. Church services in the digital era require smart, careful and targeted strategies. This research used qualitative approach, with a descriptive type of research. Data collection techiques are through interviews, observation and documentation. This paper aims to examine the leadership strategies of the Chairman of GKE Bukit Hindu Congregation Council to maximing church services in the era after the covid-19 pandemic. Through this research, it can be concluded that the Chairman of GKE Bukit Hindu utilizing various technology and communication platform, such as through social media available in the era, including Whatsapp, Youtube, Facebook, Instagram, etc. Furthermore, in his leadership, the Chairman of GKE Bukit Hindu Congregation Council uses a situasional leadership approach, while still being imbued with a Christian leadership philosophy based on Christian value, in an effort to create digital service that are able to answer the needs of congregation members to continue fellowshipping and growing in faith, in the midst of various societal contexts.